Business Students’ Insights into Their Development of Ethical Decision-Making - Mladenovic, Rosina (Journal of business ethics, 2019)
Motivated by the call for more research on students’ perceptions of their ethical development in business education programs, this study examines students’ reflections on how their understanding of ethics was challenged and/or changed, and what facilitated the development of ethical decision-making approaches in a first-year accounting course. The results indicate that students developed more sophisticated and contextualised views of ethical issues in business, government and social contexts including the need to consider their impact on various stakeholders. Students attributed this development to the various elements in the integrated course design including the real cases sourced in current newspaper articles, an ethical decision-making framework with various ethical perspectives, the reflective journal component and the ability to work in groups. These findings have implications for the design of effective ethics education programs in business.